Ethics in the Workplace. A Systems Perspective - Roth, William F. (Upper Saddle River, NJ Pearson Prentice Hall, 2005)
The book is written in a lively, conversational tone to simplify treatment of philosophically-complex ideas. It embedded case studies and examples to illustrate theoretical points of analysis. One of the features of the book is a constructive argument for restructuring organizations around pragmatic ethical standard.
Keywords: Philosophy